ON THE TYPOLOGY OF THE NEGATION MARKER MÂ IN MODERN ARABIC DIALECTS: KUWAITI, JORDANIAN, SUDANESE, AND YEMENI - Abdulkhaleq Ali Al-Rawafi; Tri Pujiati; Dadang Sudana (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2020)
Modern Arabic Dialects (MADs) have an identical morphological system with some similarities and differences in the choice of the negation morphemes. The main concern of this paper is to discuss the typological properties of the negation morpheme mâ- ما and its variation in four Modern Arabic Dialects (MADs), JA (Jordanian Arabic), KA (Kuwaiti Arabic), SA (Sudanese Arabic), and YA (Yemeni Arabic) taking into account two negation strategies identified by Brustad (2000), namely Verbal Negation and Predicate Negation. Specifically, the study will shed light on the types and positions of the negation morphemes regarding VN and PN strategies. The study employed a descriptive-analytical approach. The data were taken from previous studies on negation in MADs and online sources, i.e., published articles and YouTube. The study found that when the negation morpheme mâ - ما is used as a one-negation system or a two-negation system, as a verbal and predicate negation, it changes to the negation morpheme mâ- ما due to phonological conditions and its pre-verbal position. The study concluded that three negation templates might be generalized in the four dialects, namely one-morpheme template, two-morpheme-template, and predicate negation template. Moreover, blocking of the negation morpheme movement in the sentences happens to do to phonological conditions.